1998
DOI: 10.1136/jcp.51.6.471
|View full text |Cite
|
Sign up to set email alerts
|

Disappointing dipstick screening for urinary tract infection in hospital inpatients.

Abstract: Aim-To compare the performance of leucocyte esterase and nitrite dipstick tests with microscopic examination and culture of first morning urines (n = 420) of hospital inpatients. Results-The sensitivity, specificity, and negative predictive value of the leucocyte esterase test for the cutoV of > 10 WBC/µl were 57%, 94%, and 68%, respectively. For > 5 WBC per high power field (HPF) these variables were 84%, 90%, and 93%. For > 10 5 colony counts/ml, the sensitivity of the nitrite test was 27%, specificity 94%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 6 publications
1
5
1
1
Order By: Relevance
“…In this study, we found a very high NPV with a less than 5 % false negative rate (1 %). This degree of false negativity was much lower than that experienced by Zaman et al [16].…”
Section: Discussioncontrasting
confidence: 55%
“…In this study, we found a very high NPV with a less than 5 % false negative rate (1 %). This degree of false negativity was much lower than that experienced by Zaman et al [16].…”
Section: Discussioncontrasting
confidence: 55%
“…Zaman et al reported the sensitivity and specificity of the nitrite dipstick test in diagnosing UTI in hospitalized inpatients to be 27% and 94%, respectively (6). The sensitivity is pretty low but the specificity is high.…”
Section: Usefulness and Limitations Of Sensitivity And Specificitymentioning
confidence: 99%
“…Os problemas da próstata fazem com que a incidência volte a aumentar no sexo masculino logo após a 5ª e 6ª décadas de vida. Já no sexo feminino, passa a ser mais evidenciada no período que compreende da idade pré-escolar à fase adulta, onde nesta última, está associada com atividades sexuais, gestação e menopausa (ZAMAN, 1998).…”
Section: Introductionunclassified